The Effect of Pocket Money, Peers and Self-Control on Financial Management on Treasure Fans In Karawang - Ardinengsih, Sri Herlina; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (Westscience Press, 2024)
Treasure fans engage in activities related to the group, including merchandise purchases, concert tickets, and various other forms of support. This study aims to determine pocket money, peers, self-control and financial management. Know the correlation between pocket money, peers and self-control. Knowing the partial influence of pocket money variables, peers and self-control on financial management. As well as knowing the simultaneous influence of pocket money, peers and self-control on financial management. This research method is descriptive quantitative analysis of the SPSS V.26 helpline. Respondents used a total sample of 76 people with the criteria of Treasure fans, aged 12 – 20 years, domiciled in Karawang and have purchased official or unofficial Treasure merchandise. Based on the results of research that has been conducted, it was found: (1) the variable of pocket money from the results of respondents' answers obtained was in the affirmative category. Peer variables showed the criterion of agreeing. Self-control variables indicate strongly agreeable criteria. As well as financial management variables show strongly agreeable criteria. (2) There is a correlation between pocket money and peers has a positive correlation direction and a fairly strong correlation relationship. There is a correlation between pocket money and self-control has a positive correlation direction and a fairly strong correlation relationship. There is a correlation between peers and self-control has a positive correlation direction but a weak correlation relationship. (3) There is a partial effect of pocket money on financial management. There is a partial influence of peers on financial management. There is a partial influence of self-control on financial management. (4) There is a simultaneous influence between pocket money, peers and self-control on financial management.